The Effectiveness of Tai Chi on Stress Levels in Older Adults - Amila Widati; Widya Nurcahyaningtyas (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Stress is one of the most common psychological problems among older adults and contributes to various health disorders, such as hypertension, sleep disturbances, cognitive decline, and an increased risk of mortality. Chronic stress in older adults is also known to be closely associated with a decline in psychological well-being and quality of life. In addition, stress can exacerbate the degenerative diseases commonly experienced by older adults. Research shows that stress contributes to the onset of chronic diseases such as hypertension in older adults, making it a complex and multidimensional health issue Purpose: To analyze the effectiveness of Tai Chi exercises on stress levels in older adults Methods: A pre-experimental, single-group pretest-posttest design was conducted on 28 older adults using the PSS-10. The Tai Chi intervention consisted of 40-minute sessions, three times per week for 21 days. Analysis was performed using a paired t-test based on the study results Results: The mean stress score decreased from 15.96 ± 5.71 to 12.46 ± 3.47. The paired t-test revealed a statistically significant difference (t = 4.274; p < 0.000). Conclusion: Tai Chi is effective in reducing stress levels in the elderly and should be considered as a community nursing intervention.